2022
DOI: 10.3390/ijms231911693
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acetate versus Citrate Dialysates on Intermediary Metabolism—A Targeted Metabolomics Approach

Abstract: Acetate is widely used as a dialysate buffer to avoid the precipitation of bicarbonate salts. However, even at low concentrations that wouldn’t surpass the metabolic capacity of the Krebs tricarboxylic acid (TCA) cycle, other metabolic routes are activated, leading to undesirable clinical consequences by poorly understood mechanisms. This study aims to add information that could biologically explain the clinical improvements found in patients using citrate dialysate. A unicentric, cross-over, prospective targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Acetate also activates nitric oxide which causes vasodilatation [ 4 ]. The clinical manifestation of the BAA is an arterial pressure decrease and a heart rate increase [ 5 ]. Their study has shown that certain categories of patients with AKI after CS have lower rates of acetate metabolism [ 2 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetate also activates nitric oxide which causes vasodilatation [ 4 ]. The clinical manifestation of the BAA is an arterial pressure decrease and a heart rate increase [ 5 ]. Their study has shown that certain categories of patients with AKI after CS have lower rates of acetate metabolism [ 2 ].…”
mentioning
confidence: 99%
“…Replacing acetate by hydrochloric acid in SBD is a promising alternative; however, it is only done in a minority of cases [ 2 ]. Acetate is widely used as a weak acid acting as a dialysate buffer, thus avoiding this precipitation [ 5 ]. Even at the low concentrations (3–4 mmol/L) used, it reaches blood levels higher than physiological [ 5 ], leading to undesirable outcomes by poorly understood mechanisms [ 5 ].…”
mentioning
confidence: 99%